The society of shame - Roper, Jane, 1974- (Anchor Books, a division of Penguin Random House, 2023)
"In this timely and witty combination of So You've Been Publicly Shamed and Where'd You Go, Bernadette? a viral photo of a politician's wife's "feminine hygiene malfunction" catapults her to unwanted fame in a story that's both a satire of social media stardom and internet activism, and a tender mother-daughter tale. Kathleen Held's life is turned upside down when she arrives home to find her house on fire and her husband on the front lawn in his underwear. But the scandal that emerges is not that Bill, who's running for Senate, is having a painfully cliched affair with one of his young staffers: it's that the eyewitness photographing the scene accidentally captures a period stain on the back of Kathleen's pants. Overnight, Kathleen finds herself the unwitting figurehead for a social media-centered women's right movement, #YesWeBleed. Humiliated, Kathleen desperately seeks a way to hide from the spotlight. But when she stumbles upon the Society of Shame--led by the infamous author Danica Bellevue--Kathleen finds herself part of a group who are all working to change their lives after their own scandals. Using the teachings of the society, Kathleen channels her newfound fame as a means to reap the benefits of her humiliation and reclaim herself. But as she ascends to celebrity status, Kathleen's growing obsession with maintaining her popularity online threatens her most important relationship IRL: that with her budding activist daughter, Aggie. Hilarious and heartfelt, The Society of Shame is a pitch-perfect romp through politics and the perils of being "extremely online"-without losing your sanity or your true self"--